Analysis and Experiment on the Limitations of Static and Dynamic Transaural Reproduction with Two Frontal Loudspeakers - LIU, Lulu; XIE, Bosun (Archives of Acoustics, 2021)
By duplicating the binaural pressures of an actual source, transaural reproduction with two frontal loudspeakers is expected to recreate a virtual source in arbitrary direction. However, experiments indicated that in static transaural reproduction, the perceived virtual source is usually limited to the frontalhorizontal plane. The reasons for this limitation, as guessed, are that, in static reproduction, the dynamic cues for front-back and vertical localisation are incorrect, and the high-frequency spectral cues are unstable with head movement. To validate this hypothesis, the variations of ITD (interaural time difference) caused by head turning in both static and dynamic transaural reproductions are analysed. The results indicate that dynamic reproduction is able to create appropriate low-frequency ITD variations, and the static transaural reproduction is unable to do so. Psychoacoustic experiments are conducted to compare virtual source localisation in static and dynamic reproductions. The results indicate that dynamic reproduction is able to recreate the front, back, and vertical virtual source for low-pass stimuli below 3 kHz, while for full audible bandwidth stimulus, appropriate low-frequency dynamic cue and unstable high-frequency spectral cues in dynamic reproduction result in two splitting virtual sources.